Are 20% of Patients Actually Dissatisfied Following Total Knee Arthroplasty? A Systematic Review of the Literature - DeFrance, Michael J.; Scuderi, Giles R. (The Journal of arthroplasty, 2023)
Total knee arthroplasty (TKA) is among the most performed orthopaedic surgeries in the United States with at least 1,000,000 cases performed per year. Dissatisfaction following TKA has often been reported as 20% or more, with a multitude of causes including sociodemographic, preoperative, and postoperative factors. The purpose of this study was to re-examine the rate and causes of dissatisfaction following TKA. A systematic review of the literature was performed searching databases from 2010 to 2022. Only primary TKA cases were included and all cases of unicompartmental arthroplasty and revisions were excluded. After abstracts were reviewed, 35 articles were selected for a full-length review, which was ultimately reduced to 21 articles for final inclusion. The average rate of patient dissatisfaction was 10%. Excluding complications, the average rate of dissatisfaction was 7.3%. The most common sociodemographic factors for dissatisfaction were age < 65 years, lower income, and non-White patients. Preoperative factors included lower Kellgren-Lawrence scores, depression/anxiety, and pain catastrophizing. Postoperatively, most dissatisfaction was due to complications, unmet expectations, persistent pain, and stiffness. Based on our review, the average rate of patient dissatisfaction following TKA is 10%. Improved counseling for known risk factors may have reduced dissatisfaction rates by increasing preoperative patient optimization. Many studies in recent years have demonstrated the issue of poor patient coping skills, such as pain catastrophizing and anxiety/depression as a common cause of dissatisfaction. Ultimately, dissatisfaction following TKA still continues to affect a high portion of patients but less than historical reports of 20%.